Early Jurassic high‐Mg andesites in the Quxu area, southern Lhasa terrane: Implications for magma evolution related to a slab rollback of the Neo‐Tethyan Ocean. (16th August 2018) - Wang, Chao; Ding, Lin; Zhang, Li‐Yun; Ding, Xiang‐Li; Yue, Ya‐Hui
Abstract : Over the past few years, an increasing number of Early Jurassic magmatic rocks have been found in the southern Lhasa terrane and well studied; however, high‐Mg andesitic rocks are considerably rare, and the Mesozoic palaeotectonic framework of Neo‐Tethyan Ocean remains controversial. The present study focuses on Early Jurassic high‐Mg andesites that outcropped in the Quxu area, southern Lhasa terrane. In the Quxu area, the Early Jurassic (189 Ma) volcanic sequences are mainly composed of andesites and basaltic andesites and are unconformably in contact with Late Triassic diorites (226 Ma). These volcanic rocks are characterized by SiO2 (49–58 wt.%), MgO (6.2–11.1 wt.%) and Mg# (61–69), TiO2 (0.48–0.76 wt.%) and TFeO/MgO ratios (0.80–1.13), with geochemical features similar to those of high‐Mg andesites. Their depleted mantle‐type Nd ( ε Nd ( t ) = +4.9 to +6.9) and Hf ( ε Hf ( t ) = +9.6 to +14.9) isotopic compositions, together with their geochemical characteristics, suggest that the Quxu high‐Mg andesites were most likely produced by the interaction between the asthenospheric mantle and lithospheric mantle that metasomatized by slab‐derived fluids. The diorites belong to metaluminous calc‐alkaline series with highly positive ε Hf ( t ) values (+13.4 to +15.8) and are interpreted to be produced mainly by partial melting of the juvenile crustal basaltic rocks with minor input from the depleted mantle. We speculate that, in combination with the distribution of the Mesozoic magmatic rocks in the southern Lhasa terrane, the rollback of the subducting Neo‐Tethyan Ocean was the prime reason for the Early Jurassic tectono‐magmatic evolution in the southern Lhasa terrane. This process facilitated a rapid linear upwelling of the asthenospheric mantle beneath the southern Lhasa terrane and ultimately led to the large‐scale magmatic flare‐ups. Furthermore, events associated with slab rollback likely played an important role in crustal growth in the southern Lhasa terrane.